The Phosphidosilicates SrSi7P10 and BaSi7P10. Issue 4 (9th November 2020) - Haffner, Arthur; Weippert, Valentin; Johrendt, Dirk
Abstract : The new phosphidosilicates SrSi7 P10 and BaSi7 P10 were synthesized by solid‐state reactions, and their crystal structures determined by single‐crystal X‐ray diffraction [ P 1, Z = 1, SrSi7 P10 : a = 6.1521(1) Å, b = 8.0420(2) Å, c = 8.1374(2) Å, α = 106.854(1)°, β = 99.020(1)°, γ = 105.190(1)°; BaSi7 P10 : a = 6.1537(1) Å, b = 8.0423(2) Å, c = 8.1401(2) Å, α = 106.863(1)°, β = 99.050(1)°, γ = 105.188(1)°]. The compounds crystallize in a new triclinic structure type with vertex sharing SiP4 tetrahedra, which assemble a non‐centrosymmetric diamond‐like network of T2 supertetrahedra. The alkaline earth cations reside in cuboctahedral voids. 31 P solid‐state MAS‐NMR spectra confirm the crystal structure. SrSi7 P10 and BaSi7 P10 exhibit the lowest charged SiP network in phosphidosilicates so far. Full‐potential DFT calculations classify both compounds as semiconductors with small indirect bandgaps of 1.1 eV. Abstract :